Early stage of criminal procedure development in Old Rus' - O.A. Tarnavsky (Ученые записки Казанского университета: Серия Гуманитарные науки)
In this paper, the most promising options for developing the modern criminal procedure of Russia in the system of state penal policy were considered based on the analysis of the mutual influence exercised by the legal customs of Old Rus’ and the Byzantine canon traditions. Various methods were used in the course of the study: periodization of historical and legal processes that defined the emergence and subsequent development of criminal procedure; historical and genetic approach in order to date the moment when the first legal relations of a criminal nature occurred in Old Rus’; classification method to summarize the characteristics of legal phenomena and events associated with the emergence of criminal procedure. Based on the thorough investigation of a number of historical documents, it was concluded that criminal law and procedure of the indictment type had already existed in the pre-Christian era of the Old Russian state, due to the impact of the Hellenic legal culture. They were codified in the Rus’ Justice, an ancient legal code of the Russian state.